Large Lung Volumes Delay the Onset of the Physiological Breaking Point During Simulated Diving - McCulloch, Paul F.; Gebhart, B. W.; Schroer, J. A. (Frontiers in Physiology, 2021)
During breath holding after face immersion there develops an urge to breathe. The point that would initiate the termination of the breath hold, the “physiological breaking point”, is thought to be primarily due to changes in blood gases. However we theorized that other factors, such as lung volume, also contributes significantly to terminating breath holds during face immersion. Accordingly, 9 naïve subjects (controls) and 7 underwater hockey players (divers) voluntarily initiated face immersions in room temperature water at Total Lung Capacity (TLC) and Functional Residual Capacity (FRC) after pre-breathing air, 100% O2, 15% O2 / 85% N2, or 5% CO2 / 95% O2. Heart rate (HR), arterial blood pressure (BP), end-tidal CO2 (etCO2), and breath hold durations (BHD) were monitored during all face immersions. The decrease in HR and increase in BP were not significantly different at the two lung volumes, although the increase in BP was usually greater at FRC. BHD was significantly longer at TLC (54 ± 2 s) than at FRC (30 ± 2 s). Also, with each pre-breathed gas BHD was always longer at TLC. We found no consistent etCO2 at which the breath holding terminated. BDHs were significantly longer in divers than in controls. We suggest that during breath holding with face immersion high lung volume acts directly within the brainstem to actively delay the attainment of the physiological breaking point, rather than acting indirectly as a sink to produce a slower build-up of PCO2.